DETERMINANTS OF SUCCESSFUL IMPLEMENTATION OF E-GOVERNMENT SYSTEM - Katharina Yuneti; Dodik Ariyanto; A.A.N.B Dwirandra; I Gde Ary Wirajaya (Jurnal Akuntansi dan Pajak, 2022)
To determine the effect of the determinants of the success of the implementation of the Local Government Information System using the DeLone and McLean model is the purpose of this study. Questionnaires were distributed to obtain data. Purposive sampling method with a total sample of 80 sample. Path analysis using Partial Least Square is a data analysis technique used. It is proven in the research, namely that the belief system of information quality affects the system use, while service quality, social factors and system quality, has no effect on system use. The results also show that system trust, information quality, social factors affect system user satisfaction, while service quality and system quality have no effect on user satisfaction. Then, it also proves that user satisfaction and system use affect individual performance. The success of this system is measured based on user satisfaction with and as a result of the application of the system and individual efforts, so that the implementation of the Local Government Information System in all regions of the Regional Apparatus Organization in Kupang Regency is quite successful.